Evidence for electronic gap-driven metal-semiconductor transition in phase-change materials - Shakhvorostov, D.; Nistor, R.; Krusin-Elbaum, L.; Martyna, G.; Newns, D.; Elmegreen, B.; Liu, X.; Hughes, Zak; Paul, S.; Cabral, C.; Raoux, S.; Shrekenhamer, D.; et al. (National Academy of Sciences, 2009)
Phase-change materials are functionally important materials that can be thermally interconverted between metallic (crystalline) and semiconducting (amorphous) phases on a very short time scale. Although the interconversion appears to involve a change in local atomic coordination numbers, the electronic basis for this process is still unclear. Here, we demonstrate that in a nearly vacancy-free binary GeSb system where we can drive the phase change both thermally and, as we discover, by pressure, the transformation into the amorphous phase is electronic in origin. Correlations between conductivity, total system energy, and local atomic coordination revealed by experiments and long time ab initio simulations show that the structural reorganization into the amorphous state is driven by opening of an energy gap in the electronic density of states. The electronic driving force behind the phase change has the potential to change the interconversion paradigm in this material class.